2022
DOI: 10.1111/aos.15101
|View full text |Cite
|
Sign up to set email alerts
|

Topical noninvasive retinal drug delivery of a tyrosine kinase inhibitor: 3% cediranib maleate cyclodextrin nanoparticle eye drops in the rabbit eye

Abstract: Purpose: Tyrosine kinase inhibitors inhibit VEGF receptors. If delivered to the retina, they might inhibit oedema and neovascularization such as in age-related macular degeneration and diabetic retinopathy. The aim of this study was to formulate cediranib maleate, a potent VEGF inhibitor, as γ-cyclodextrin nanoparticle eye drops and measure the retinal delivery and overall ocular pharmacokinetics after a single-dose administration in rabbits. Methods: A novel formulation technology with 3% cediranib maleate as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Cediranib levels obtained in the retina were 100 times higher than the reported IC 50 value of the type-II VEGF receptor. This study demonstrated the ability of cyclodextrin to act as a permeability enhancer for ocular protein and peptide delivery …”
Section: Novel Approaches For the Delivery Of Protein And Peptidesmentioning
confidence: 78%
See 1 more Smart Citation
“…Cediranib levels obtained in the retina were 100 times higher than the reported IC 50 value of the type-II VEGF receptor. This study demonstrated the ability of cyclodextrin to act as a permeability enhancer for ocular protein and peptide delivery …”
Section: Novel Approaches For the Delivery Of Protein And Peptidesmentioning
confidence: 78%
“…This study demonstrated the ability of cyclodextrin to act as a permeability enhancer for ocular protein and peptide delivery. 176 5.1.1.2. Chelating Agents.…”
Section: Novel Approaches For the Delivery Of Protein And Peptidesmentioning
confidence: 99%